Exploring coronial determination of intent for poisoning-related deaths in Australia, 2001-2013 - Kate Churruca; Rebecca Mitchell (BMC, 2017)
Abstract Background In countries like the United States and the United Kingdom, systematic variation in the classification of intent in pharmaceutical poisoning deaths have been identified between jurisdictions. This study aimed to explore whether the coronial determination of intent (unintentional, intentional, undetermined) for pharmaceutical-related poisoning deaths may have affected death rates over time and by jurisdiction in Australia. Methods A retrospective examination of mortality records in the National Coronial Information System (NCIS) during 1 January 2001 to 31 December 2013 was conducted. The NCIS is a national internet-based data storage and retrieval system for deaths that were notified to a coroner. Pharmaceutical deaths due to unintentional, intentional or undetermined intent were identified using the NCIS classification. Proportions of the different intent classifications and the mortality rates by intent over time were compared between jurisdictions. Results There were 17,895 pharmaceutical-related poisoning deaths in Australia between 2001 and 2013 that had closed cases in the NCIS. Proportions of deaths classified as unintentional (48.3-66.3%), intentional (24.7-35.9%) and undetermined (6.7-24.7%) varied significantly among Australian jurisdictions. There were significant increases in the rate of classification of unintentional poisoning for some states, and significant increases in intentional poisoning classification in Western Australia, and decreases in New South Wales and Victoria. There was no significant change in classification of undetermined intent. Conclusions Significant variation in classifications of intent, both between state jurisdictions and over time, may be the result of regional differences in demographics and increases in prescription drug misuse. However, the inconsistent use of 'undetermined' intent between state jurisdictions suggests coroners may experience varying difficulty in retrospectively ruling on intent in the equivocal circumstances of pharmaceutical poisoning. The widespread use of psychological autopsy may assist coroners to classify intent, while the implementation of new classifications for pharmaceutical poisoning death may overcome some of the inherent difficulty in intent classification and improve the potential for injury surveillance irrespective of intent.